(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To study the effectiveness of Hayman suture technique to control postpartum hemorrhage. Method: Hayman suture was applied in 43 cases. A No-1 Vicryl suture was used on a round body or a straight needle. In 36 cases (83.72%) Hayman suture was the only intervention. In 4 cases (9.30%) uterine vessels and ovarian vessels were also ligated along with Hayman suture. In 3 cases (7%), along with Hayman suture, Gunashilas circumferential sutures were taken. Results: None of the 43 patients required hysterectomy. Conclusion: Hayman suture technique is an easily and rapidly applied, effective, simple, safe, life saving and fertility preserving method to control atonic postpartum hemorrhage. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 14-17